1993
DOI: 10.1113/expphysiol.1993.sp003678
|View full text |Cite
|
Sign up to set email alerts
|

Renal micropuncture study of the effects of D‐glucose tubular calcium handling in the anaesthetized rat

Abstract: SUMMARYTracer microinjection studies were used to grossly locate the nephron site of altered calcium transport following D-glucose loading. Superficial proximal and distal nephrons were injected with a solution containing 45Ca and either D-glucose or L-glucose (as control). Tubule calcium transport was assessed from the recovery of radioactivity in the final urine. 45Ca recoveries from early proximal microinjections were comparable in the two groups (2-63 + 0 68 vs. 3-70 + 1l19 %). However, 45Ca recoveries fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As mentioned earlier, previous micropuncture and microperfusion studies demonstrated calcium reabsorption defect in the TAL in diabetic animals. [6][7][8] Our study has ruled out changes in paracellin-1 gene expression as a possible cause of diabetes-associated TAL defect in renal calcium and magnesium reabsorption. As insulin is known to increase transepithelial potential difference (Vt) in TAL, 13 it is possible that the lack of insulin in diabetes may reduce Vt, thus suppressing calcium and magnesium reabsorption.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As mentioned earlier, previous micropuncture and microperfusion studies demonstrated calcium reabsorption defect in the TAL in diabetic animals. [6][7][8] Our study has ruled out changes in paracellin-1 gene expression as a possible cause of diabetes-associated TAL defect in renal calcium and magnesium reabsorption. As insulin is known to increase transepithelial potential difference (Vt) in TAL, 13 it is possible that the lack of insulin in diabetes may reduce Vt, thus suppressing calcium and magnesium reabsorption.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to osmotic effect, a specific tubular defect in calcium reabsorption, which leads to calcium loss, has been proposed. [6][7][8] Though most ultrafiltered calcium is reabsorbed in the proximal tubules, 9 previous microperfusion studies did not reveal any decrease of calcium reabsorption in this segment in diabetic animals. [6][7][8] In fact, two sites have been identified as having defect in calcium transport: the thick ascending limb (TAL) of Henle's loop and terminal nephron.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…An increase in tubular glucose could reduce renal handling of calcium which is directly dependent on tubular reabsorption of glucose (19). Indeed, blockading tubular glucose reabsorption by phloridzine prevented hypercalciuria and microinjection of D-glucose in rat nephron increased calciuria (26). However, in our study, the higher calciuria was associated with a decrease in filtered glucose following insulin bolus (Fig.…”
Section: Caiciuria Induced By a Decrease In Tr0mentioning
confidence: 44%
“…The hypercalciuric response to glucose in the rat results from a reduced tubular reabsorption of calcium (Garland & Singh, 1988). Recent microinjection studies in our laboratory (Singh & Garland, 1985;Boland & Garland, 1990) have shown that this may in some way relate to the raised intratubular glucose concentration. In these studies the effect of D-glucose has been compared to that of L-glucose or D-mannitol as a control.…”
Section: Introductionmentioning
confidence: 99%